Endogenous formaldehyde turnover in humans compared with exogenous contribution from food sources. (18th February 2014) - ,
Abstract: The FEEDAP Panel received a request to deliver a scientific opinion on the safety and efficacy of formaldehyde used in feed for all animal species based on dossiers submitted by applicants. In parallel, the ANS Panel evaluated the safety of formaldehyde formed from endogenous production and from dietary sources of methanol, including aspartame. In order to support both evaluations, assistance was requested to the SCER unit to evaluate the oral internal dose of formaldehyde in humans from endogenous production, food‐derived from target animals exposed to formaldehyde‐treated feed and formaldehyde generated from dietary sources of methanol, including from food additives such as aspartame. Endogenous turnover of formaldehyde was estimated to be approximately 0.61‐0.91 mg/kg bw per minute and 878–1310 mg/kg bw per day assuming a half life of 1 1.5 min. Compared with formaldehyde turnover and the background levels of formaldehyde from food sources (1.7‐1.4 mg/kg b. w per day for a 60–70 kg person), including from dietary methanol, the relative contribution of exogenous formaldehyde from consumption of animal products (milk, meat) from target animals exposed to formaldehyde‐treated feed was negligible (<0.001 %). Oral exposure to formaldehyde from aspartame involves metabolism to methanol and further oxidation to formaldehyde. At the current ADI of 40 mg/kg bw per day for aspartame, formaldehyde would be approximately 4 mg/kg bw per day and represent only 0.3‐0.4 % of the endogenous turnover of formaldehyde.